2018
DOI: 10.1590/1414-431x20187599
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin induces growth inhibition and apoptosis in human gastric carcinoma cells by enhancement of p53 expression and function

Abstract: The tumor suppressive role of oridonin, an active compound extracted from Rabdosia rubescens, has been proven in several gastric cancer (GC) cell lines. The present study aimed to evaluate the effect of oridonin on another GC cell line, SNU-216, and explore the potential mechanisms. The viable cell numbers, cell migration, survival fraction, and cell viability were, respectively, evaluated by trypan blue exclusion assay, wound healing assay, clonogenic assay, and CCK-8 assay. Cell apoptosis was determined by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…On the other hand, expression of p21 cip1/waf1 and DR5 was significantly increased in bortezomib-treated cells even without noticeable change in p53 at early time point. Oridonin, a herbal diterpenoid, increased expression of p53 and Bax in SNU-216 cells, demonstrating its inducibility and functionality in the cells 29. Therefore, it is conceivable that bortezomib might activate an alternative signaling pathway that obviates p53 induction to upregulate DR5 and p21 cip1/waf1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, expression of p21 cip1/waf1 and DR5 was significantly increased in bortezomib-treated cells even without noticeable change in p53 at early time point. Oridonin, a herbal diterpenoid, increased expression of p53 and Bax in SNU-216 cells, demonstrating its inducibility and functionality in the cells 29. Therefore, it is conceivable that bortezomib might activate an alternative signaling pathway that obviates p53 induction to upregulate DR5 and p21 cip1/waf1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is a glycoprotein that plays an important role in physiological processes such as proliferation, apoptosis and differentiation of cell by activating the calcium signaling pathway, MAPK signaling pathway and PI3K/AKT signaling pathway ( Carlisle et al., 2007 ). As an important anticancer gene, the inactivation of p53 plays an important role in tumor formation, and increasing studies have found that the p53 plays a crucial role in retarding tumor cell cycle, promoting tumor cell apoptosis and inhibiting tumor angiogenesis ( Bi et al., 2018 ; Li P. et al., 2019 ; Wang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the change of TP53 mRNA level was not the reason for the enhanced expression of p53 in NB cells. And, this finding is inconsistent with a previous report in gastric cancer cells . This may be due to the fact that cells of different origins respond differently to oridonin: gastric cancer cells originate from epithelial cells and NB cells originate from neural crest.…”
Section: Discussionmentioning
confidence: 99%
“…And, this finding is inconsistent with a previous report in gastric cancer cells. 22 This may be due to the fact that cells of different origins respond differently to oridonin: gastric cancer cells originate from epithelial cells and NB cells originate from neural crest. Mdm2 is the major negative regulator of p53, for it can promote the degradation of p53 by increasing its ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation